2014
DOI: 10.1007/s10639-014-9361-5
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers’ experiences of ICT in daily life and in educational contexts and their proto-technological pedagogical knowledge

Abstract: Many pre-service teachers are members of the net generation and are expected to be familiar with different ICTs, yet several studies have indicated that they are not necessarily able to use them for teaching and learning. The notion of teachers' technological pedagogical knowledge (TPK) is central to this concern. In this study we use the responses of 146 pre-service teachers to open-ended questions about the experiences and knowledge of ICT and pedagogy they brought with them when they entered university teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
11
0
3
Order By: Relevance
“…A persistent question in the development of education programmes for online teachers is as follows: what balance of online knowledge domains -among pedagogy, content and technology -has the most likelihood of success? Research also suggests that the order in which subjects are taught -pedagogy, content, technology and others -has some bearing on the successful development of self-efficacy in online teachers (Chai, Koh, and Tsai 2010;Graham, Borup, and Smith 2012;Kontkanen et al 2016); as such, it may be beneficial to examine the structure of entire teaching programmes instead of focusing on individual courses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A persistent question in the development of education programmes for online teachers is as follows: what balance of online knowledge domains -among pedagogy, content and technology -has the most likelihood of success? Research also suggests that the order in which subjects are taught -pedagogy, content, technology and others -has some bearing on the successful development of self-efficacy in online teachers (Chai, Koh, and Tsai 2010;Graham, Borup, and Smith 2012;Kontkanen et al 2016); as such, it may be beneficial to examine the structure of entire teaching programmes instead of focusing on individual courses.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers recommended that technology instruction should be integrated with both methodological and content instruction to maximise teacher self-efficacy. Other studies suggested that lack of content knowledge hindered the TPACK development of the self-efficacy of pre-service teachers (Graham, Borup, and Smith 2012) to the extent that one study eliminated it altogether (Kontkanen et al 2016). One successful TPACK-based online teacher certificate programme did not reflect a content integration challenge; however, it was a master level programme (MA) where pedagogical self-efficacy and content self-efficacy may already have been developed (Moore-Adams and Jones 2015).…”
Section: Changes In Self-efficacymentioning
confidence: 99%
“…Prospective teachers consider internet as an inseparable part of their life both in school environment and outside of it (Yılmaz, 2012) and take advantage of internet for the following purposes; researching (Yavuz-Mumcu & Dönmez-Usta, 2014),downloading data, receiving and sending e-mail, supervising and using databases, website designing for educational purposes, making telephone conversations (Şahin and Schreglmann, 2012), playing games, downloading music and movies (Arabacıoğlu and Dursun, 2015), communicating in social media, on-line purchasing, reading newspaper, determination of destination, transactions of banking and finance . Regarding the technology acceptance and usage situations, the following are emphasized; technology acceptance and usage levels between teachers and prospective teachers are reasonable statistically (Teo, 2015), prospective teachers consider themselves adequate in technology (Çetin, Çalışkan, & Menzi, 2012), user-friendliness perception affects the attitudes of prospective teachers towards usage intention and computer utilization while ease of use perception doesn't affect these attitudes (Teo, Ursavaş, & Bahçekapılı (2011), technology acceptance and usage intention in education don't differ in terms of grade level and sex variables (Efe, 2011;Teo, Fan, & Du, 2015), individual learning experiences with technology are limited (Kontkanen, Dillon, Valtonen, Renkola, Vesisenaho, & Vaisanen, 2014) but they affect educational technology usage intentions (Efe, 2011), and knowledge, ability and confidence deficiencies in technology acceptances affect ICT self-efficacy negatively (Bozdoğan & Özen, 2014).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In general, an e-learning system is considered to be successful if it can replicate classroom experience and consider the students' needs (Kontkanen et al 2014;Sriram 2014). Therefore, it is important to understand the factors that drive the users' intention to participate in e-learning.…”
Section: Introductionmentioning
confidence: 99%